Robert Frank's The Americans : the art of documentary photography - Day, Jonathan (Intellect, 2011)
In the mid 50s, Swiss-born New Yorker Robert Frank embarked on a ten-thousand-mile road trip across post-war America, capturing thousands of photographs of all levels of a rapidly changing society. The resultant photo-book, The Americans, represents a seminal moment in both photography and in America's emerging understanding of itself. To mark the book's fiftieth anniversary, Jonathan Day revisits this pivotal work and contributes a thoughtful and revealing critical commentary. Though the importance of The Americans has been widely acknowledged, it still retains much of its mystery. This compr.